Processing of Thermoplastic Polyurethane Nanocomposite via Reactive Extrusion - Khairatun Najwa, Mohd Amin; Pratheep, K. Annamalai; Darren, J. Martin (2014)
Recently, nanocomposites of TPU have been developed with the inclusion of several nanoparticles. This paper demonstrates the preparation of TPU nanocomposites with renewable nanoparticles,microcrystalline cellulose (MCC), Initially, MCC was dispersed in water and was sonicated. The composites have been prepared by dispersing MCC in polyol precursor using a proprietary method, and further polymerized with diisocyanate and chain extender precursors via reactive extrusion processing.